Integrating ICT in English Language Teaching and Learning in Indonesia - Hidayati , Tuti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2016)
Indonesian ELT is complex for numerous reasons, and the level of students' outcome has been regarded unsatisfactory by a number of researchers and academics. This paper considers ICT as one of possible alternatives to deal with the complexity of Indonesian ELT and to improve its outcomes. It widely explores ICT integration in English LTL, especially on how ICT has been used in this field. It further investigates the benefits and challenges of integrating ICT in LTL. The paper argues that the integration of ICT is promising for changing and improving the effectiveness of the current Indonesian ELT condition when it is carried out in line with the effective LTL principles. The integration of ICT will enable teachers to vary teaching and learning activities, to gradually change the teaching style to be more student-centred, to train students to have more active role in learning, and to access a huge range of authentic learning materials. The paper also acknowledges the contraints that will emerge in an effort of integrating ICT in Indonesian English LTL. Hence, some recommedations for action are proposed at the end.